The Relationship Between Absolute Poverty Income Inequality in Rural and Urban Areas in Indonesia: The Granger Causality Approach - Candra Mustika; Haryadi Haryadi; Junaidi Junaidi; Zamzami Zamzami (Jurnal Ekonomi Pembangunan, 2022)
This study aims to determine the relationship between poverty and inequality in rural and urban areas by using the Granger causality test approach. This research method uses the Granger causality test analysis tool with rural and urban areas as objects in all provinces in Indonesia with use data from thirty four province and period year from 2014 until 2020. The results of the Granger causality test for rural areas show that there is a realtionship unidirectional relationship between poverty and inequality, the relationship shows significant inequality that causes poverty in rural areas, that meaning in rural area absolute poverty happen because inequality income distribution, while the results of causality tests for urban areas show that there is no relationship at all between poverty and inequality in the urban areas. that meaning In urban areas no causality between absolute poverty and inequality income distribution, this result shows that poverty and inequality in urban areas do not contain a direct one way or two-way relationship.